ANALISIS PENOKOHAN PADA TOKOH WISANGGENI SECARA ANALITIS DAN DRAMATIK DALAM CERITA PENDEK BERJUDUL “HONOR CERITA PENDEK” KARYA HASTA INDRIYANA - Dani Muhamad; Robi Sugara; Rosi Rosi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The aims of research for  (1) discuss the results of characterization analysis on the character of Wisanggeni in short story titled "Honor cerita pendek" analytically, and (2) to describe Wisanggeni characterization dramatically. The short story of Hasta Indriyana will be analyzed descriptively qualitatively. The research steps include: (1) reading short story "Honor cerita pendek", (2) analyzing characterization of Wisanggeni figure in the short story, then (3) describing character analytically and dramatically. Based on the results of the analysis, it can be seen that Hasta Indriyana created characterization of Wisanggeni with the technique of depiction of figures analytically and dramatically.